Comprehensive genetic diversity revealed in the pre-breeding RILs (O. sativa × O. rufipogon) with enhanced yield and pigmented grain quality - Roy, Subhas Chandra; Shil, Pankaj (Frontiers in Genetics, 2025)
Developing high-yielding rice varieties (Oryza sativa L.) is critical to ensure global food security. The narrow genetic base in the released rice varieties has plateaued the improvement. Considering the potentials of wild rice (Oryza rufipogon), two distinct recombinant inbred line (RIL) populations were developed through interspecific hybridization (BWF: Badshabhog × O. rufipogon and CWF: Chenga × O. rufipogon) to increase the genetic base via alien introgression of hidden genes. Genetic diversity was assessed through the following: genetic variability parameters, broad-sense heritability, Mahalanobis D2 test, and principal component analysis (PCA) using 15 agro-morphological characteristics that indicated enhanced genetic variation. The first four principal components (PCs) together accounted for 73.74% of the variability in BWF, and the first six PCs showed 71.90% cumulative variability in CWF (eigen value >1). The broad-sense heritability ranged from 74.42% to 99.87% for all traits in both the RILs. Single plant yield was positively correlated with grain per panicle, 1,000 grain weight, grain length, and panicle weight. The cluster analysis showed that the grain per panicle, grain weight, kernel breadth, and plant height were the key yield-contributing traits. The detection of petunidin 3-O-glucoside through HR-LCMS-QTOF indicated that anthocyanin was synthesized in the black-grain RILs, signifying nutritional improvement. Hence, underutilized wild rice contributed immensely to enhancing the genetic base of the RILs, with unusual genetic diversity associated with yield improvement and grain pigmentation. Pre-breeding materials are the cornerstone of future rice improvement programs, and our materials can be efficiently utilized to develop resilient, productive, and nutritious pigmented rice varieties.